2022
DOI: 10.1111/jfbc.14510
|View full text |Cite
|
Sign up to set email alerts
|

Polygonatum sibiricum ameliorated cognitive impairment of naturally aging rats through BDNF–TrkB signaling pathway

Abstract: Cognitive dysfunction is high in the elderly population and seriously affects the quality of life. Brain‐derived neurotrophic factor (BDNF) is one of the key neurotrophic proteins, and activation of BDNF–TrkB is considered an effective strategy to improve cognitive dysfunction during aging. In this study, administration of polygonatum sibiricum (PS) for 5 months effectively ameliorates the cognitive function, improving the Nissl body state in cortex and hippocampus in aging rats. In addition, PS can improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Learning and memory processes are mainly associated with complex neuropathological and biochemical changes. Cognitive dysfunction is relatively high in the elderly population, which seriously affects the quality of life [106]. In naturally aged rats, Polygonati Rhizomacould effectively ameliorated cognitive function, improved Nissl body state in cortex and hippocampus, improved synaptic structure, increased the number of synapses, reversed the reduction of postsynaptic density protein 95 (PSD-95) and synaptophysin, as well as up-regulated the expression of brain-derived neurotrophic factor (BDNF) via BDNF-TrkB signaling pathway [106].…”
Section: Benefits Towards Neurological Diseasementioning
confidence: 99%
“…Learning and memory processes are mainly associated with complex neuropathological and biochemical changes. Cognitive dysfunction is relatively high in the elderly population, which seriously affects the quality of life [106]. In naturally aged rats, Polygonati Rhizomacould effectively ameliorated cognitive function, improved Nissl body state in cortex and hippocampus, improved synaptic structure, increased the number of synapses, reversed the reduction of postsynaptic density protein 95 (PSD-95) and synaptophysin, as well as up-regulated the expression of brain-derived neurotrophic factor (BDNF) via BDNF-TrkB signaling pathway [106].…”
Section: Benefits Towards Neurological Diseasementioning
confidence: 99%
“…This formula comprises two herbal components: Polygonatum sibiricum Redouté (Chinesse name:Huang Jing) and Lycium chinense Mill (Chinesse name:Gou Qi), known for their benefits in kidney nourishment, essence replenishment, and aging delay ( Yang et al, 2021 ). Furthermore, contemporary pharmacological investigations have confirmed that Huang Jing and Gou Qi enhance learning and memory in AD models, reduce Aβ deposition in the brain, and mitigate aging ( Ye et al, 2015 ; Yao et al, 2018 ; Luo et al, 2022 ; Zhang et al, 2022 ). Despite EJW’s proven efficacy in AD treatment, its mechanistic basis remains elusive.…”
Section: Introductionmentioning
confidence: 97%
“…It has been shown to regulate immunity, improve memory, act as an antioxidant, delay aging, protect the cardiovascular system, lower blood sugar levels, regulate lipid levels, and exhibit anti-tumor properties. [11][12][13] Previous studies have demonstrated that Polygonatum can enhance cognitive ability in models of Alzheimer's disease 14 and mitigate β-amyloidinduced neurotoxicity. 15 However, its therapeutic mechanism has not been extensively studied, and further research is required.…”
Section: Introductionmentioning
confidence: 99%